PENGARUH PERSEPSI SISWA TENTANG KETERAMPILAN MENGAJAR GURU DAN LINGKUNGAN BELAJAR TERHADAP MOTIVASI BERPRESTASI SISWA - Solichah, Siti; Witurachmi, Sri; ., Jaryanto (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThe objectives of this research are to investigate: (1) the effect of students perceptions about the teaching skills of teachers on the student achievement motivation, (2) the effect of the learning environ-ment on the student achievement motivation, and (3) the interaction of effects between the students per-ceptions of teaching skills of teachers and learning environment on the student achievement motivation. The method is used quantitative causal relationship. Its population was all class XI student of Accounting Program in the academic year 2016. The samples of the research were determined through the saturated sampling technique. The data are collected through questionnaire and analyzed by using multiple linear regression analysis with the computer program of SPSS at the significance level of 5%.The results of re-search are as follows: (1) There is a positive and significant effect of the students perceptions about the teaching skills of teachers on the student achievement motivation (tstat > tcrit or 4.662 > 1.986) at the signif-icance value of 0.000 (2) There is a positive and significant effect of the environment learning on the stu-dent achievement motivation (tstat > tcrit or 5.478 > 1.986) at the significance value of 0.000 (3) there is a positive and significant interaction of effects between the students perceptions about the teaching skills of teachers and learning environment on the student achievement motivation (Fstat> Fcrit or 33.976 â¥ 3.094) at the significance value 0,000. The regression equation Y = -5.365 + 0,248X1 + 0,223X2. The relative contribution of studentsâ perceptions of teaching skills of teachers was 42.35%. The relative contribution of the learning environment was 57.65%. The effective contribution of studentsâ perceptions of teaching skills of teachers was 19.90%. Effective contribution to the learning environment was 27.10%.Keyword :perceptions of teachersâ teaching skills, learning environment, student achievement motivationABSTRAKPenelitian ini bertujuan untuk menguji ada tidaknya: (1) pengaruh persepsi siswa tentang ket-erampilan mengajar guru terhadap motivasi berprestasi siswa, (2) pengaruh lingkungan belajar terhadap motivasi berprestasi siswa, dan (3) pengaruh persepsi siswa tentang keterampilan mengajar guru dan ling-kungan belajar terhadap motivasi berprestasi siswa. Metode penelitian yang digunakan adalah kuantitatif hubungan kausal. Populasi penelitian ini adalah seluruh siswa kelas XI Program Keahlian Akuntansi tahun pelajaran 2016/2017. Teknik pengambilan sampel dalam penelitian ini adalah menggunakan sampel jenuh. Metode pengumpulan data dengan menggunakan angket serta dianalisis dengan menggunakan analisis re-gresi linier berganda dengan program SPSS dengan taraf signifikansi 5%. Hasil dari penelitian: (1) Ter-dapat pengaruh yang positif dan signifikan persepsi siswa tentang keterampilan mengajar guru terhadap motivasi berprestasi siswa (thitung > ttabel atau 4,662 > 1,986) dengan nilai signifikansi 0,000, (2) Terdapat pengaruh yang positif dan signifikan lingkungan belajar terhadap motivasi berprestasi siswa (thitung > ttabel atau 5,478 > 1,986) dengan nilai signifikansi 0,000, (3) Terdapat pengaruh yang positif dan signifikan per-sepsi siswa tentang keterampilan mengajar guru dan lingkungan belajar terhadap motivasi berprestasi siswa (Fhitung > Ftabel atau 33,976 â¥ 3,094) dengan nilai signifikansi 0,000. Persamaan regresi Y = -5,365 + 0,248X1 + 0,223X2. Sumbangan relatif persepsi siswa tentang keterampilan mengajar guru sebesar 42,35%. Sumbangan relatif lingkungan belajar sebesar 57,65%. Sumbangan efektif persepsi siswa tentang keterampilan mengajar guru sebesar 19,90%. Sumbangan efektif lingkungan belajar sebesar 27,10%.Kata Kunci:persepsi keterampilan mengajar guru, lingkungan belajar, motivasi berprestasi siswa